Preparation of a Designed Poly(trimethylene carbonate) Microvascular Network by Stereolithography. Issue 12 (15th October 2014) - Schüller‐Ravoo, Sigrid; Zant, Erwin; Feijen, Jan; Grijpma, Dirk W.
<x xml:space="preserve">Abstract</x> Designed flexible and elastic network structures are prepared by stereolithography using a photo‐crosslinkable resin based on a poly(trimethylene carbonate) (PTMC) macromer with a molecular weight of 3150 g/mol. Physical properties and the compatibility with human umbilical vein endothelial cells (HUVECs) are evaluated. The hydrophobic networks are found to be flexible and elastic, with an E modulus of 7.9 ± 0.1 MPa, a tensile strength of 3.5 ± 0.1 MPa and an elongation at break of 76.7 ± 0.7%. HUVECs attach and proliferate well on the surfaces of the built structures. A three‐dimensional microvascular network is designed to serve as a perfusable scaffold for tissue engineering. In the design, 5 generations of open channels each branch into 4 smaller channels yielding a microvascular region with a high density of capillaries. The overall cross‐sectional area through which medium or blood can be perfused remains constant. These structures would ensure efficient nourishment of cells in a large volume of tissue. Built by stereolithography using the PTMC resin, the smallest channels of these structures have square cross‐sectional areas, with inner widths of approximately 224 μm and wall thicknesses of approximately 152 μm. The channels are open, allowing water to perfuse the scaffold at 0.279 ± 0.006 mL/s at 80 mmHg and 0.335 ± 0.009 mL/s at 120 mmHg.